1987
DOI: 10.1148/radiology.162.1.3786766
|View full text |Cite
|
Sign up to set email alerts
|

Ferrite particles: a superparamagnetic MR contrast agent for enhanced detection of liver carcinoma.

Abstract: The potential of superparamagnetic ferrite particles to enhance detection of liver carcinoma at magnetic resonance (MR) imaging was studied with in vitro MR spectroscopy and in vivo MR imaging in animal models. After intravenous administration of ferrite, MR spectroscopy showed selective shortening of T2 relaxation times in normal liver but not in tumor. MR imaging showed that ferrite produced profound signal loss only from normal liver and not tumor; thus, differences in signal intensity between liver and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(52 citation statements)
references
References 0 publications
1
50
0
1
Order By: Relevance
“…SPIO are ingested by macrophages of the RES, resulting in signal loss in normal tissue [8, 9]. SPIO-MRI is an imaging modality that is different from CTAP/CTHA and iv-CT which demonstrate alterations is blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPIO are ingested by macrophages of the RES, resulting in signal loss in normal tissue [8, 9]. SPIO-MRI is an imaging modality that is different from CTAP/CTHA and iv-CT which demonstrate alterations is blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…SPIO are ingested by macrophages of the reticuloendothelial system (RES), resulting in signal loss in normal tissue. Metastases and some malignant liver tumors, having no RES, retain their signal intensity and can be distinguished from the normal liver [8, 9]. It has been reported that SPIO-MRI is an efficacious modality for the diagnosis of focal liver lesions [10, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…It can be injected intravenously as a bolus for imaging HCC [40]. SPIO acts as a negative contrast agent because SPIO particles are taken up by Kupffer cells in the reticuloendothelial system of the liver [41,42], causing a local magnetic field inhomogeneity and resulting in considerable T2* shortening [42]. SPIO-enhanced MR is reported to be sensitive in detecting HCC [43,44,45].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Superparamagnetic iron oxide (SPIO), which is taken up by Kupffer cells in the liver and by macrophages in the spleen, is a tissue-specific MRI agent [5, 6]. Mergo and Ros [7] demonstrated that well-differentiated hepatocellular carcinomas (HCCs) took up a greater amount of SPIO than less differentiated HCCs, possibly because of the greater proportion of Kupffer cells in well-differentiated HCCs.…”
Section: Introductionmentioning
confidence: 99%